2004
DOI: 10.1111/j.0953-816x.2004.03333.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fronto‐parietal coupling of brain rhythms in mild Alzheimer's disease: a multicentric EEG study

Abstract: Cholinergic deafferentation/recovery in rats mainly impinges on the fronto-parietal coupling of brain rhythms [D. P. Holschneider et al. (1999) Exp. Brain Res., 126, 270-280]. Is this reflected by the functional coupling of fronto-parietal cortical rhythms at an early stage of Alzheimer's disease (mild AD)? Resting electroencephalographic (EEG) rhythms were studied in 82 patients with mild AD and in control subjects, such as 41 normal elderly (Nold) subjects and 25 patients with vascular dementia (VaD). Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 53 publications
14
118
0
3
Order By: Relevance
“…The ␦ rhythm has been implicated in slow-wave sleep (16) and in supporting normal awake physiological functions (37,38). For example, Babiloni et al (37) reported that interhemispheric and frontoparietal ␦ band synchronization is reduced in patients with mild Alzheimer's disease and vascular dementia compared with normal subjects. Animal studies have suggested a role for the ␦ rhythm in subcortical EEG synchronization (39,40).…”
Section: (Abbreviations As Inmentioning
confidence: 99%
“…The ␦ rhythm has been implicated in slow-wave sleep (16) and in supporting normal awake physiological functions (37,38). For example, Babiloni et al (37) reported that interhemispheric and frontoparietal ␦ band synchronization is reduced in patients with mild Alzheimer's disease and vascular dementia compared with normal subjects. Animal studies have suggested a role for the ␦ rhythm in subcortical EEG synchronization (39,40).…”
Section: (Abbreviations As Inmentioning
confidence: 99%
“…The following frequency bands were studied: delta (2-4Hz), theta (4 -8Hz), alpha 1 (8 -10.5Hz), alpha 2 (10.5-13Hz), beta 1 (13-20Hz), and beta 2 (20 -30Hz) in line with previous EEG studies on dementia 17,19,[71][72][73][74][75][76][77] Of note, sharing of a frequency bin by two contiguous bands is a widely accepted procedure. 19,73,-91 Choice of fixed EEG bands did not account for individual alpha frequency (IAF) peak, defined as the frequency associated with the strongest EEG power at the extended alpha range.…”
Section: Spectral Analysis Of the Electroencephalogram Datamentioning
confidence: 99%
“…In most of these studies a consistent decrease of coherence in the alpha and beta band was reported, whereas results for other bands were more variable. Abnormalities of functional connectivity have also been demonstrated with nonlinear synchronization methods (Jeong et al, 2001;Stam et al, 2002Stam et al, , 2006Pijnenburg et al, 2004;Babiloni et al, 2004). While these studies in general support the hypothesis of a disconnection syndrome in Alzheimer's disease, two problems need further attention: (i) assessment of functional connectivity with EEG and MEG can be biased by volume conduction, which may yield spurious correlations between nearby sensors and hence render interpretation unreliable; (ii) connectivity studies in Alzheimer's disease are generally very descriptive and lack a more robust framework to discriminate between normal and abnormal networks in the brain.…”
Section: Introductionmentioning
confidence: 98%